Mucosal and systemic immune responses induced by intranasal immunization of recombinant Bacillus subtilis expressing the P97R1, P46 antigens of Mycoplasma hyopneumoniae. Issue 10 (15th October 2019) - Wang, Yongheng; Wang, Jialu; Zhou, Mengyun; Liu, Peng; Zhang, En; Li, Yuchen; Lin, Jian; Feng, Zhixin; Yang, Qian
Abstract: Mycoplasma hyopneumoniae ( M. hyopneumoniae ) is the pathogen of swine enzootic pneumonia, a chronic respiratory disease affecting pigs of all ages. The ciliated epithelial cells of the respiratory tract are the main target invaded and colonized by M. hyopneumoniae. Therefore, the ideal vaccine would be mucosally administered and able to stimulate suitable mucosal immunity and prevent the adherence of pathogens to mucosal cell surfaces . Currently, Bacillus subtilis as a recombinant vaccine carrier has been used for antigen delivery and proved to be effectively enhancing the innate immunity of nasal mucosa. Here, our study attempts to construct recombinant Bacillus subtilis (B.S-P97R1, B.S-P46), which can express the P97R1 or P46 antigen of M. hyopneumoniae, and to evaluate the immune responses in BALB/c mice. Initially, we respectively successfully constructed recombinant B.S-P97R1, B.S-P46 and validated the expression of antigen proteins by Western analysis. Then, recombinant B.S-P97R1 or B.S-P46 were respectively intranasally (i.n.) immunized in mice. Both strong P97R1-specific and P46-specific immunoglobulin G (IgG), secretory immunoglobulin A (SIgA) antibodies were induced in sera, bronchoalveolar lavage fluids (BALs) by ELISA analysis. Moreover, the levels of specific IL-4, IFN-γ in the immunized mice were elevated, and the proliferation of lymphocytes was also enhanced. In general, intranasal inoculation of recombinant B.S-P97R1 or B.S-P46 resulted in strong mucosal immunity, cell-mediated and humoral immunity, which was a mixed Th1/Th2-type response. In addition, our results provided a potential novel strategy that may be applied to the development of vaccines against M. hyopneumoniae .